Phase effects in masking by harmonic complexes in birds - Lauer, Amanda M. (2006)
Masking by harmonic complexes depends on the frequency content of the masker and its phase spectrum. Harmonic complexes created with negative Schroeder phases (component phases decreasing with increasing frequency) produce more masking than those with positive Schroeder phases (increasing phase) in humans, but not in birds. The masking differences in humans have been attributed to interactions between the masker phase spectrum and the phase characteristic of the basilar membrane. In birds, the similarity in masking by positive and negative Schroeder maskers, and reduced masking by cosine-phase maskers (constant phase), suggests a phase characteristic that does not change much along the basilar papilla. To evaluate this possibility, the rate of phase change across masker bandwidth was varied by systematically altering the Schroeder algorithm. Humans and three species of birds detected tones added in phase to a single component of a harmonic complex. As observed in earlier studies, the minimum amount of masking in humans occurred for positive phase gradients. However, minimum masking in birds occurred for a shallow negative phase gradient. These results suggest a cochlear delay in birds that is reduced compared to that found in humans, probably related to the shorter avian basilar epithelia.